Inhaled [D-Ala2]-Dynorphin 1-6 Prevents Hyperacetylation and Release of High Mobility Group Box 1 in a Mouse Model of Acute Lung Injury - Vladislav N. Karkischenko; Veronika I. Skvortsova; Melik T. Gasanov; Yuriy V. Fokin; Maxim S. Nesterov; Nataliya V. Petrova; Oxana V. Alimkina; Igor A. Pomytkin (Journal of Immunology Research)
COVID-19 is a respiratory infection caused by the SARS-CoV-2 virus that can rapidly escalate to life-threatening pneumonia and acute respiratory distress syndrome (ARDS). Recently, extracellular high mobility group box 1 (HMGB1) has been identified as an essential component of cytokine storms that occur with COVID-19; HMGB1 levels correlate significantly with disease severity. Thus, the modulation of HMGB1 release may be vital for treating COVID-19. HMGB1 is a ubiquitous nuclear DNA-binding protein whose biological function depends on posttranslational modifications, its redox state, and its cellular localization. The acetylation of HMGB1 is a prerequisite for its translocation from the nucleus to the cytoplasm and then to the extracellular milieu. When released, HMGB1 acts as a proinflammatory cytokine that binds primarily to toll-like receptor 4 (TLR4) and RAGE, thereby stimulating immune cells, endothelial cells, and airway epithelial cells to produce cytokines, chemokines, and other inflammatory mediators. In this study, we demonstrate that inhaled [D-Ala2]-dynorphin 1-6 (leytragin), a peptide agonist of δ-opioid receptors, significantly inhibits HMGB1 secretion in mice with lipopolysaccharide- (LPS-) induced acute lung injury. The mechanism of action involves preventing HMGB1’s hyperacetylation at critical lysine residues within nuclear localization sites, as well as promoting the expression of sirtuin 1 (SIRT1), an enzyme known to deacetylate HMGB1. Leytragin’s effects are mediated by opioid receptors, since naloxone, an antagonist of opioid receptors, abrogates the leytragin effect on SIRT1 expression. Overall, our results identify leytragin as a promising therapeutic agent for the treatment of pulmonary inflammation associated with HMGB1 release. In a broader context, we demonstrate that the opioidergic system in the lungs may represent a promising target for the treatment of inflammatory lung diseases.